A escravidão nas pinturas brasileiras de Nicolas-Antoine Taunay (1816-1821) - Covre, Barbara Dantas Batista (2023)
This thesis presents the paintings that the French artist Nicolas-Antoine Taunay produced during his stay in Rio de Janeiro, between 1816 and 1821. The main objective is to analyse the iconography of slavery, using the image-text relationship, with emphasis on linking textual and visual sources. The painter brought to Brazil his experience as a Court and State painter, as a participant in the French Revolution and as an artist of Napoleon Bonaparte. Famous in Paris and discredited in Brazil, he produced what the Portuguese monarch installed in the Court of Rio paid him to do: landscapes and portraits. In landscapes, the iconography of slavery is complex, one of its characteristics is the connection with previous experiences and models, in addition to becoming a visual message of English philosophers and French philosophes against the servitude and slavery that were in vogue at their time, in Paris and in Rio. As a philosopher painter, Taunay presents the philosophical, artistic, and moral debates of his time. The Iconographic analysis identifies the work that slaves performed, the bonds of submission in sociopolitical relations and the economic importance of black slavery and African trafficking. His idyllic and exotic canvases, aimed at an audience that is still culturally and artistically connected to Absolutism, are documentary scenarios that present the typical elements of nature and the city of Rio de Janeiro. To show the customs of the inhabitants, Taunay presents the American paradise ruled by D. João as a tropical version of the Old Regime, with an emphasis on servile social relations, the depreciation of the black ethnic group and enrichment by slave labour. The painter saw the servants of Europe as slaves in Brazil and, to represent them, he sought known images, ancient symbols, in addition to his view of life in the Court of Rio. Against the grain of a West that fought the transatlantic trade in human beings, Nicolas-Antoine Taunay's paintings help to understand that Rio de Janeiro was the most slave-owning city in the Americas during the Johannine period.